2019
DOI: 10.4103/ijnmr.ijnmr_205_17
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy status and its relationship with quality of life among nurses in teaching hospitals of Shiraz University Of Medical Sciences

Abstract: Background:Health literacy can be considered as a factor affecting healthcare providers' decision-making. The aim of this study was to investigate health literacy status and its relationship with quality of life among the nurses working in teaching hospitals affiliated with Shiraz University of Medical Sciences in Iran.Materials and Methods:This cross-sectional study was conducted in 2017. To this end, 185 nurses from hospitals were selected by stratified random sampling. The data collection instruments includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…More importantly, this substandard documentation practice is associated with prolonged hospital stays of the patients and increased patient mortality ( Mathioudakis et al, 2016 ; Rossetti et al, 2013 ; Rothman et al, 2012 ). This finding is consistent with a study done in Indonesia ( Motea et al, 2016 ), Iran ( Aghdam et al, 2009 ), and European hospitals ( Ausserhofer et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, this substandard documentation practice is associated with prolonged hospital stays of the patients and increased patient mortality ( Mathioudakis et al, 2016 ; Rossetti et al, 2013 ; Rothman et al, 2012 ). This finding is consistent with a study done in Indonesia ( Motea et al, 2016 ), Iran ( Aghdam et al, 2009 ), and European hospitals ( Ausserhofer et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…Health literacy is the ability to acquire, process, and conceive basic health-related information and services [ 8 ]. Based on the definition provided by the World Health Organization (WHO), HL is a complex of social and cognitive abilities to acquire, understand, and apply health-related information to promote health and maintain good health [ 9 ]. It has been confirmed that people with higher levels of HL have more information about their health status [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…All nurse educators should emphasize the importance of health literacy skills for themselves and their patients. Another three studies showed that health literacy skills impact the ability of nurses to deal with problems, such as stress management, positive thinking, spiritual wellbeing, and quality of life ( 11 , 31 , 34 ). Therefore, educating patients on health literacy skills becomes crucial to enhance their quality of life and health outcomes.…”
Section: Resultsmentioning
confidence: 99%